The Application Of The Principle Of Bank Secrecy In The Process Of Eradicating Money Laundering Criminal Offences Based On Aspects Of Legal Certainty - Rahman Maulana, Dyo; Ahmad Sholikhin Ruslie (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Bank secrecy is the core of a banking system policy and is based on the